2023
DOI: 10.1111/nph.19014
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana rosette habit is controlled by combined light and energy signaling converging on transcriptional control of the TALE homeobox gene ATH1

Abstract: In the absence of light signals, Arabidopsis plants fail to develop the rosette habit typical for this species. Instead, plants display caulescent growth due to elongation of rosette internodes. This aspect of photomorphogenic development has been paid little attention and molecular events involved, downstream of photoreceptor signaling, remain to be identified.Using a combination of genetic and molecular approaches, we show that Arabidopsis rosette habit is a photomorphogenic trait controlled by induction of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…The ARK2 gene, involved in tubulin formation and plant morphogenesis [41,42], and the HEMA2 gene, encoding a key enzyme in the chlorophyll synthesis pathway [43], were also downregulated, potentially contributing to the altered plant architecture and photosynthetic pigment content. On the other hand, the upregulation of the DOGT1 gene, which glucosylates brassinosteroids and leads to a BR-deficient phenotype when overexpressed [44], and the ATH1 gene, a transcription factor involved in photomorphogenesis and flowering time regulation [45, 46], may be responsible for the dwarf and compact phenotype and delayed flowering observed in PCZ-treated choy sum.…”
Section: Resultsmentioning
confidence: 99%
“…The ARK2 gene, involved in tubulin formation and plant morphogenesis [41,42], and the HEMA2 gene, encoding a key enzyme in the chlorophyll synthesis pathway [43], were also downregulated, potentially contributing to the altered plant architecture and photosynthetic pigment content. On the other hand, the upregulation of the DOGT1 gene, which glucosylates brassinosteroids and leads to a BR-deficient phenotype when overexpressed [44], and the ATH1 gene, a transcription factor involved in photomorphogenesis and flowering time regulation [45, 46], may be responsible for the dwarf and compact phenotype and delayed flowering observed in PCZ-treated choy sum.…”
Section: Resultsmentioning
confidence: 99%
“…However, Borniego et al (2022) showed that genes that were described as thermosensors in shoots (phytochrome B, PIF7, EARLY FLOWERING 3) do not fulfil the same function in the root, adding a new layer of complexity to the system and addressing a question that interests me immensely, which is the sitespecificity of signalling cascades. Another recent paper that I particularly liked was Hajibehzad et al (2023), where they evaluated the regulation of the rosette growth habit of Arabidopsis. This paper appealed to me because it addresses an important question, which is how environmental signals control meristem activity.…”
Section: What Motivates You On a Day-to-day Basis?mentioning
confidence: 99%